DESIGN AND DEVELOPMENT OF E-COMMERCE WEBSITE CASE STUDY : PET TOY SHOP - Sriviphat, Thawanrat; Nasongsri, Pitchaya; Jonkhun, Songkran (Chalermkarnchana Academic Journal, 2024)
Currently, the sale of products is limited to customers purchasing items directly at the store, without an online sales channel. Therefore, the project developers aim to add an online sales channel for the Pet Toy Shop to reach a more diverse consumer base. The project team conducted research on building a website using Visual Studio Code, which is a platform for website content management capable of creating websites. Additionally, XAMPP was used to assist in developing the website, enabling the Pet Toy Shop to sell products online without consumers needing to visit the store in person. The online sales website for bags was developed using Visual Studio Code for system development and XAMPP for the database. Customer satisfaction with the website was assessed using questionnaires, and data analysis was performed using percentage (%), mean (X̄), and standard deviation (S.D.) through statistical software. The project results indicated that the website for online bag sales had an average satisfaction rating of 3.21, indicating a high level of satisfaction.